2012
DOI: 10.1016/j.coph.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The roles of purinergic signaling during gastrointestinal inflammation

Abstract: Extracellular purines play important roles as neurotransmitters and paracrine mediators in the gastrointestinal (GI) tract. Inflammation of the GI tract causes marked changes in the release and extracellular catabolism of purines, and can modulate purinoceptor expression and/or signaling. The functional consequences of this include suppression of the purinergic component of inhibitory neuromuscular and neurovascular transmission, increased release of purines from immune and epithelial cells, loss of enteric ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 92 publications
1
28
0
5
Order By: Relevance
“…**p<0.01, compared with control group, ## p<0.01, compared with VHM group [31][32][33]. It was reported that the colonic distention irritation increased the expression of P2X 7 receptor in sacral spinal cord of rats, whereas pretreatment with P2X 7 receptor antagonists inhibited the nociceptive transmission of visceral pain induced by the intraperitoneal injection of acetic acid and the visceral pain response of the model rats, suggesting that P2X 7 receptor has a facilitating effect in visceral painful transmission [34][35][36]. Our experimental results showed that the expression of P2X 7 at both mRNA and protein levels in the DRG of the model rats was significantly increased in comparison with that in the control group, indicating that P2X 7 receptor in DRG was involved in the transmission of nociceptive signal induced by the continuous CRD stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…**p<0.01, compared with control group, ## p<0.01, compared with VHM group [31][32][33]. It was reported that the colonic distention irritation increased the expression of P2X 7 receptor in sacral spinal cord of rats, whereas pretreatment with P2X 7 receptor antagonists inhibited the nociceptive transmission of visceral pain induced by the intraperitoneal injection of acetic acid and the visceral pain response of the model rats, suggesting that P2X 7 receptor has a facilitating effect in visceral painful transmission [34][35][36]. Our experimental results showed that the expression of P2X 7 at both mRNA and protein levels in the DRG of the model rats was significantly increased in comparison with that in the control group, indicating that P2X 7 receptor in DRG was involved in the transmission of nociceptive signal induced by the continuous CRD stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…In this case, exogenously added compounds should be potent enough to elicit an inhibitory effect and able to mimic the physiological route of relaxation. This might be relevant if studies performed with animal models of inflammation lacking purinergic neuromuscular transmission (Strong et al, 2010;Roberts et al, 2012) have translation to human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the aim of this paper is to establish a pharmacological methodology to characterize the receptor involved in endogenous purinergic responses and to investigate which of the exogenously added purines better mimics the neurotransmitter. This can be used in future studies where P2Y 1 agonists might be useful to treat purinergic motor disorders (Strong et al, 2010;Roberts et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Purinergic neuromuscular transmission to the vascular and circular smooth muscle is reduced during experimental colitis in mice and rats (Antonioli et al 2010;Neshat et al 2009;Roberts et al 2012). ACh released from submucosal vasomotor neurons binds to endothelial muscarinic receptors, which stimulates endothelial NO synthase.…”
Section: Effects Of Colitis On the Ensmentioning
confidence: 99%